Lineage and Virtue in Josephus: The Respective Roles of Priestly Worldview and Roman Culture - Berthelot, Katell (Journal of ancient Judaism, 2020)
This article assesses the importance of lineage and virtue in Josephus’ notions of Jewish nobility and the Jewish people. Furthermore, it investigates the respective roles of Josephus’ priestly education and his exposition to Roman culture in his use of such concepts. I argue that while Josephus adopted some aspects of Roman or Greco-Roman discourses on nobility, such as the notion that true nobility goes along with virtue, he resisted the Roman sociopolitical view of nobility, because he tended to identify Jewish aristocracy with the priesthood and thus stuck to a genealogical model. By contrast, Josephus’ definition of the kinship (oikeiotēs) that unites the members of the Jewish people as based either on birth/common ancestors or on choice (the choice to live under Jewish laws, implicitly characterized as virtuous) in Against Apion reflects the impact on the Judean historian of Roman citizenship grants and the pro-Roman discourses that praised this policy.